Ti50Cu25Ni20Sn5 bulk metallic glass fabricated by powder consolidation - Choi, P. P.; Kim, J. S.; Nguyen, O. T. H.; Kwon, Y. S. (ELSEVIER SCIENCE BV, 2007)
A bulk metallic glass of Ti50Cu25Ni20Sn5 nominal composition was produced via a powder metallurgical route, namely the preparation of glassy powders by mechanical alloying followed by their consolidation by spark-plasma sintering. Samples were characterized with respect to their structure and thermal properties before and after sintering. A bulk glassy sample, having nearly full density and containing only a small fraction of the intermetallic NiTi2 phase, could be obtained after careful selection of sintering parameters. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: AMORPHOUS-ALLOYS; SUPERCOOLED LIQUID; EXTRUSION; STRENGTH